2021
DOI: 10.1097/pec.0000000000002567
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Level as a Predictor of Outcome in Patients Admitted to Pediatric Intensive Care Units

Abstract: The aim of this study was to assess serum albumin level on admission to the pediatric intensive care unit (PICU) as a prognostic indicator. Methods: A prospective study was conducted in Fayoum UniversityChildren's Hospital. The study subjects' demographics and clinical and laboratory data were recorded. Pediatric Risk of Mortality III (PRISM-III) score was calculated. Serum albumin level was assessed within 24 hours from admission. Outcomes included mortality, PICU and hospital stay, need and duration of mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that increasing the serum ALB is an effective means of reducing the mortality rate of patients. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that increasing the serum ALB is an effective means of reducing the mortality rate of patients. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…In a large prospective study, a decrease in albumin levels of 25 g/L was associated with an increase in morbidity of 55%. Consistently, albumin concentrations have also been shown to be associated with poor clinical outcomes in critically ill children ( 2 , 14 ). Each increase of 10 g/L in serum albumin in critically ill children is associated with a 73% reduction in the risk of 60-day mortality (hazard ratio = 0.27; 95% CI: 0.14–0.51) ( 2 ).…”
Section: Discussionmentioning
confidence: 87%
“…Each increase of 10 g/L in serum albumin in critically ill children is associated with a 73% reduction in the risk of 60-day mortality (hazard ratio = 0.27; 95% CI: 0.14–0.51) ( 2 ). In a recent study, albumin levels still showed a negative association with mortality in patients admitted to the PICU (OR = 0.289; 95% CI: 0.136–0.615) ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reported that low serum albumin level was associated to poor outcomes in critically ill patients [12,13]. Also, in children with nephrotic syndrome serum albumin level < 1.5gm/dl was found to be an independent risk factor for all types of infection [14].…”
Section: Introductionmentioning
confidence: 95%